KONSTRUKSI MAKNA MAHASISWI SEBAGAI SPG (SALES PROMOTION GIRL) FREELANCE DI KOTA PEKANBARU - Lolyna, Arfryani; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Freelance SPG is one type of side jobs are much interested by the female students. In Pekanbaru itself, this phenomenon among student quite rapidly because the Event Organizer (EO) is usually recruit student as their SPG. This study aims to know the motive, the meaning and the student communication experiences as a freelance SPG in Pekanbaru.This study uses qualitative research with phenomenological approach. Informants in this study were 5 female students who worked as a freelance SPG who has been selective purposively. Data collection techniques is used by observation, depth interview, and documentation. To achieve the validity of the data in this study, researcher used the extension of participation and triangulation.This study shows that the motive student working as a freelance SPG past motive (because motive) is economic needs, utilizing the time, and the influence of other; as well as the motive future (in order to motive) is add work experience and get a better job. The meanings student of their jobs as a freelance SPG is a pleasant communication experience that is get a lot of new experiences, understand the character of people, receive the praise from others, as well as being more communicative; as well as the unpleasant communication experience is consumer abuse, bad responses and the views of society, and the negative stamp from society.Keyword: meaning construction, SPG freelance, motive, communication experience